Trail Trees: Living Artifacts (Vivifacts) of Eastern North America - Nicholas C. Kawa; Bradley Painter; Cailín E. Murray (Ethnobiology Letters, 2015)
Living trees historically modified by human populations, oftentimes referred to as “culturally modified trees” (CMTs), are found throughout the North American landscape. In eastern North America specifically, indigenous populations bent thousands of trees to mark trails, and some of these still exist in the region today. In this article, we present a synthesis of current knowledge on trail trees, including their speculated functions, formation, and selection. We also examine the theoretical implications of these living artifacts (or vivifacts) and how they may open new avenues for investigation by archaeologists, environmental historians, and ethnobiologists. To conclude, we make a call for expanded public recognition and documentation of trail trees, discussing the need for their incorporation into forest and park management plans.